(untitled) (Journal of Scientific Research, 2025)
Chicken eggs are an excellent source of vital nutrients, such as vitamins, minerals, carotenoids, proteins, and healthy fats. Though it can significantly fulfil the nutritional needs of adults and children, the contamination of heavy metals may cause subsequent toxicity to our bodies. The ultimate goal of the experiment is to analyze the amounts of heavy metals (Pb, Cr, Ni, Zn, and Cu) in eggs and their health risk assessments. After the egg samples were processed using a di-acid digestion technique, an AAS was used to evaluate the samples. Here, only the concentrations of Pb and Cr exceeded the maximum permissible range established by WHO/FAO. According to the health risk assessment, the metals in the study (except for Pb) did not individually represent a concern by the target hazard quotient and estimated daily intake. Pb and Cr had threshold carcinogenic risks because their CR values ranged from 10-4 to 10-6. Consumers of Ni, which has a CR > 10-4, are thought to pose a carcinogenic risk to adults and children. The quantities of zinc and copper in all examined samples were deemed acceptable for human ingestion. This research provides legislators with precise and trustworthy information to enhance food safety regulations and mitigate public health threats.